Elementary School and Spelling Bees as Sites of Struggle: Akeela and the Bee - Tessa Troughton (Canadian Society for Studies in Education, 2022)
In the popular film, "Akeela and the Bee", a struggle between power and non-power discourse unfolds in a working-class community. Akeela's determination and the cohesiveness of the community ultimately challenge the social boundaries of discourse. Representations of literacy and language are analyzed through Gee's definition of discourse and Verdoodt's notion of a Pygmalion film. Key themes found in the film are discourse in contact and conflict, the mentor/mentee relationship, community support for learning, and the negative impact of a performance-focused learning environment. Ultimately, consolidations and opportunities are proposed through critical literacy and Culturally Sustaining Pedagogy".